2015
DOI: 10.1016/j.scico.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

The Sensemaking-Coevolution-Implementation Theory of software design

Abstract: Understanding software design practice is critical to understanding modern information systems development. New developments in empirical software engineering, information systems design science and the interdisciplinary design literature combined with recent advances in process theory and testability have created a situation ripe for innovation. Consequently, this paper utilizes these breakthroughs to formulate a process theory of software design practice: SensemakingCoevolution-Implementation Theory explains… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 97 publications
0
34
0
15
Order By: Relevance
“…Fifth, both theories bring some a priori credibility. SCI originated in the SE field to explaining SE process phenomena [36]. It synthesizes highly influential previous research including…”
Section: Conceptual Evaluation Of Fbs and Scimentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, both theories bring some a priori credibility. SCI originated in the SE field to explaining SE process phenomena [36]. It synthesizes highly influential previous research including…”
Section: Conceptual Evaluation Of Fbs and Scimentioning
confidence: 99%
“…For example, when Fitzgerald [35] states, "in conventional software development, the development lifecycle in its most generic form comprises four broad phases: planning, analysis, design, and implementation" (p. 589), he is treating Waterfall as a theory.However, methods are not appropriate foundations for process theories as the former prescribe ostensibly good approaches to an activity while the latter explain the fundamental properties of an activity [10]. Therefore, this sections focuses on process theories, not methods or other prescriptions.A recent review [36] found no comprehensive software development process theories.However, it did find an engineering design process theory, the Function-Behavior-Structure Framework, which had been applied to SE, and proposed but not empirically test an alternative called Sensemaking-Coevolution-Implementation Theory (discussed next).…”
mentioning
confidence: 99%
“…In SE and ISD, the planning model underlies stage-gate or lifecycle views of the design process (Boehm, 1988;Royce, 1970), plan-driven methods (Jacobson et al, 1999;Kruchten, 2003), and the perceived need for significant upfront analysis. Meanwhile, the improvisation model underlies teleological views of the design processes (Ralph, 2013;Stacey & Nandhakumar, 2009), agile methods (Beck, 2005;Schwaber, 2004) what phases will the project pass through? Invoking IDT, a rationalist would argue that the planner may answer these questions using intuition and deduction; however, an empiricist would argue that to the extent these questions could be answered at all, they could only be answered by first building the system.…”
Section: Planning Vs Improvisingmentioning
confidence: 99%
“…An alternative to SDLC is Sensemaking-Coevolution-Implementation Theory (SCI). SCI (Ralph, 2013) posits that complex software systems are produced primarily through its three titular activities (Figure 4, Sensemaking the process where the design agent perceives its and the design object's environments and organizes these perceptions to create or to refine the mental picture of context Coevolution the process where the design agent simultaneously refines its mental picture of the design object, based on its mental picture of context, and the inverse Implementation the process where the design agent generates or updates the design object using its mental picture of the design object Of course, SDLC and SCI are not the only theories pertaining to the software development process. The Function-Behavior-Structure Framework of engineering design (FBS) posits that a design agent manipulates models of the functions (goals), behaviors and structure of an artifact to produce a detailed specification suitable for informing construction (Gero, 1990;Gero & Kannengiesser, 2004).…”
Section: Software Development Theoriesmentioning
confidence: 99%
“…Ralph [23] who estimated possible inheritances from process theories with the point of view "how and why an entity changes and develops".…”
mentioning
confidence: 99%